2011
DOI: 10.1038/leu.2011.293
|View full text |Cite
|
Sign up to set email alerts
|

An immature immunophenotype of bone marrow mast cells predicts for multilineage D816V KIT mutation in systemic mastocytosis

Abstract: D816V KIT mutation of bone marrow (BM) mast cells (MC) is a common feature to systemic mastocytosis (SM) patients. Nevertheless, occurrence of the KIT mutation in BM cell compartments other than MC is associated with progression to more aggressive forms of the disease and poor outcome in indolent SM (ISM). Here, we assessed the potential association between the immunophenotype of MC and multilineage KIT mutation in the BM of SM patients through the investigation of the flow cytometric protein expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 20 publications
(29 reference statements)
3
52
0
1
Order By: Relevance
“…Overall, 64 of 192 patients included in this study have been included in previously reported series of systemic mastocytosis patients by the REMA. [19][20][21][22] …”
Section: Patients and Samplesmentioning
confidence: 99%
“…Overall, 64 of 192 patients included in this study have been included in previously reported series of systemic mastocytosis patients by the REMA. [19][20][21][22] …”
Section: Patients and Samplesmentioning
confidence: 99%
“…Further, comprehensive immunophenotyping has shown that an immature BM MC phenotype (CD25 1 /FceRI lo /FSC lo / SSC lo /CD45 lo ), in the absence of coexisting normal MC in the BM, correlated with multilineage hematopoietic involvement by KITD816V, regardless of the WHO SM subtype [74]. In contrast, BM MC from patients with ISM subtypes displayed a mature activated MC phenotype (e.g., increased expression of MC activation markers CD63, CD69, and CD203c in patients with BMM) [75].…”
Section: Aggressive Smmentioning
confidence: 99%
“…8,27 It follows that MC from MCL may express immaturity markers such as CD123, CD34, HLA-DR, and display reduced expression of CD117 and FceRI. The immature phenotype is correlated with multilineage KIT mutations in bone marrow and a poor prognosis.…”
Section: Immunophenotypementioning
confidence: 99%
“…8 Nevertheless, the prognostic significance of these observations for predicting clinical outcome in patients with SM requires further investigation. Therapeutic options are limited and the disease is most often fatal within a few months.…”
Section: Introductionmentioning
confidence: 99%